Preferentially oriented SrTiO3 thin films grown on lanthanide-assisted Si(001) via pulsed laser deposition - Rijckaert, Hannes; Latronico, Giovanna; Deduytsche, Davy; Solano, Eduardo; Paturi, Petriina; Mele, Paolo (Royal Society of Chemistry (RSC), 2026)
The integration of high-quality SrTiO3 thin films on silicon substrates is crucial for various applications. This work investigates the use of an out-of-plane, self-oriented La2O2CO3 seed layer prepared via the chemical solution deposition (CSD) method as a template for SrTiO3 growth by pulsed laser deposition (PLD). The growth window of the SrTiO3 thin film was determined by in situ X-ray diffraction and by studying the thermal stability of the La2O2CO3 film. This study resulted in crack-free films with preferential but not exclusive (001) out-of-plane orientation when using one-step PLD deposition at 750 °C. Further in-depth X-ray diffraction analysis revealed that the SrTiO3 film exhibited multiple preferential orientations rather than a continuous fibre texture. Transmission electron microscopy confirmed a uniform SrTiO3 film without interfacial reactions and a homogeneous composition. These findings highlight the key role of deposition conditions in controlling crystallinity and orientation, enabling the integration of high-quality perovskite oxide on silicon.